Legal Rigidity vs Flexibility: Examining Qath’i and Zanni Interpretations in State-Enforced Modesty Regulations - Amin, Aminullah; Muammar Bakry; Abd. Wahid Haddade (DIKTUM: Jurnal Syariah dan Hukum, 2025)
This research discusses the issues of Qath’i and Dzhanni, exploring their essence and characteristics, as well as the problems and debates among scholars regarding these concepts. It also addresses the urgency and implications of these concepts on the extraction of legal rulings in both classical and contemporary Fiqh. This study employs a library research method, involving the analysis of various articles, journals, and books relevant to the research theme. Data collection in this research is carried out through documentation techniques, where the researcher seeks and analyzes data by studying documents written by other researchers on the topic. The discussion of Qath’i and Dzhanni is approached from two perspectives: Wurud (the arrival of the evidence) and Dalalah (the indication of the evidence). There are Qath’i al-Wurud and Dzhanni al-Wurud, as well as Qath’i al-Dalalah and Dzhanni al-Dalalah. These concepts are firmly grounded and well-established. Therefore, even if these concepts are challenged or criticized, they cannot be undermined or dismissed. Understanding and comprehending the concepts of Qath’i and Dzhanni is crucial, as they are integrated with how words indicate meanings or legal contents contained within them. This has significant implications for Fiqh as a product of ijtihad. The approach of classical Fiqh involves measuring evidence based on its numerical certainty, establishing clear meanings, and considering it to have no other possible meanings. Meanwhile, the approach of contemporary Fiqh focuses not on linguistic-semantic analysis, but on the substance of the Qur’anic verses or Hadiths.